A nickel-cobalt skin-core structure catalyst and its preparation method and application
By forming a nickel-cobalt slim core structure catalyst on a metal cobalt substrate, the problems of insufficient catalyst activity and poor structural stability are solved, and the effect of efficient preparation of high-purity FDCA under mild conditions is achieved, reducing production costs and improving safety.
Patent Information
- Application Number
- CN202211431524.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-15
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-11-15
AI Technical Summary
In FDCA production, existing catalysts have safety risks such as insufficient catalytic activity, poor structural stability and high temperature and high pressure, which are difficult to meet industrial production requirements.
Using a nickel-cobalt slim core structure catalyst, stable cobalt oxalate microwires or microrods are formed on the metal cobalt substrate by epitaxial growth method, and cobalt-nickel hydroxide is grown on its surface to form a micro-nano structure rich in catalytic active sites.
The reactivity and structural stability of the catalyst are improved, production costs are reduced, and the ability to efficiently prepare high-purity FDCA under mild conditions is achieved.
Smart Images

Figure CN118048632B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a nickel-cobalt skin-core structure catalyst and a preparation method and application thereof. Background Art
[0002] As global attention to the environment continues to increase, countries have taken many measures to reduce carbon emissions. Industrial production and energy production are the main sources of carbon emissions, and a large amount of carbon emissions from industrial and energy production mainly come from the use of fossil resources. Therefore, in order to reduce carbon emissions, it is necessary to adjust the energy structure and reduce or even replace the use of fossil resources from the perspectives of energy and materials. From the perspective of materials, it is necessary to find new materials that are renewable and can enter the carbon cycle, such as biomass materials. At present, bio-based platform compounds have also entered the promotion stage and have even partially replaced the use of petrochemical products. Taking the bio-based platform compound 2,5-furandicarboxylic acid (FDCA) as an example, its polymerization product polyethylene 2,5-furandicarboxylate (PEF) is greener and more environmentally friendly than petroleum-based polyethylene terephthalate (PET), and is also superior in gas barrier properties, melting temperature, and mechanical properties.
[0003] In the prior art, the production of FDCA is mainly based on thermal catalysis, but the reaction conditions for the thermal catalytic production of FDCA are relatively harsh, and it needs to be carried out in a high temperature and high pressure oxygen environment, and a precious metal catalyst needs to be used. Especially in actual large-scale production, the O2 pressure is usually required to be around 2MPa, which has a greater safety risk. In addition to the production of FDCA by thermal catalysis, the electrocatalytic conversion of 5-hydroxymethylfurfural (HMF) to FDCA has also received great attention. Compared with the thermal catalytic method, electrocatalysis has the advantages of milder reaction conditions and more controllable operation. Because HMF contains aldehyde groups, its chemical properties are relatively active, and it is easy to deteriorate during long-term storage, which affects the purity of the product FDCA. Selecting 2,5-furan dimethanol (BHMF) with higher chemical stability as a raw material for the preparation of FDCA will help to obtain FDCA with higher purity, but a catalyst with higher catalytic activity is required. The existing catalysts mainly have the following problems: the catalyst activity is low due to the lack of active sites exposed on the catalyst surface, which is difficult to meet the requirements for industrial production; the structural stability of the catalyst is poor, and the supported catalyst usually faces the problem of shedding, resulting in a sharp drop in catalytic activity. Summary of the invention
[0004] In view of the deficiencies of the prior art, the technical problem to be solved by the present invention is how to prepare a catalyst with stable structure, rich catalytic sites and high activity.
[0005] In order to solve the above technical problems, the first aspect of the present invention provides a nickel-cobalt skin-core structure catalyst, including a metal cobalt substrate and a micro-nano structure grown on the metal cobalt substrate, the micro-nano structure including a core layer and a skin layer wrapping the core layer, the core layer is a cobalt microwire or microrod, and the skin layer is cobalt nickel hydroxide.
[0006] The nickel-cobalt skin-core structure catalyst of the present invention has a stable micro-nano structure, which exposes more specific surface area and catalytic active sites than metal cobalt substrates, cobalt microwires, and cobalt microrods, so that the catalyst has good activity; the cobalt substrate has high conductivity, and the surface micro-nano cobalt components make the electrochemical starting potential of the catalyst lower, and the introduction of nickel components makes the catalyst have a high current density.
[0007] The second aspect of the present invention provides a method for preparing the above-mentioned nickel-cobalt skin-core structure catalyst, comprising the following steps:
[0008] S1, immersing a metal cobalt substrate in an oxalic acid solution, and growing stable cobalt oxalate microwires or microrods on the surface of the metal cobalt substrate by epitaxial growth to obtain a cobalt oxalate precursor;
[0009] S2, placing the cobalt oxalate precursor in a hydrogen atmosphere for reduction to obtain a cobalt intermediate;
[0010] S3. Immerse the cobalt intermediate in a nickel salt solution, and epitaxially grow cobalt nickel hydroxide on the surface of the cobalt microwires or microrods to obtain a nickel-cobalt skin-core structure catalyst.
[0011] The present invention obtains the nickel-cobalt micro-nano structure by epitaxial growth. The construction of the cobalt-nickel micro-nano structure greatly enhances the reaction activity of the catalyst. The prepared catalyst has excellent industrial application prospects.
[0012] In a preferred or optional embodiment, the metal cobalt substrate is selected from any one of metal cobalt foam, cobalt sheet, cobalt foil and cobalt mesh. The above preparation method can obtain a highly active catalyst without using precious metals, and the production cost is low.
[0013] In a preferred or optional embodiment, in the step S1, the molar ratio of the metal cobalt substrate to oxalic acid is 1:5.5-28.
[0014] In a preferred or optional embodiment, in step S1, the reaction time of the epitaxial growth is 0.25 to 4 hours, and the reaction temperature is 20 to 80°C.
[0015] In step S1, a structurally stable cobalt oxalate precursor can be obtained by in-situ epitaxial growth. The molar ratio of the metal cobalt substrate to oxalic acid, the reaction time and the reaction temperature of the epitaxial growth will affect the specific surface area of the material. Within the above-mentioned limited range, the surface of the cobalt substrate can grow a cobalt oxalate microwire or microrod precursor with a stable structure and sufficient specific surface area.
[0016] In a preferred or optional embodiment, the step S2 specifically comprises: placing the cobalt oxalate precursor into a tubular furnace, introducing hydrogen into the tubular furnace, heating the temperature to a set temperature after a period of time, then maintaining the temperature, and cooling the temperature to room temperature to obtain a cobalt intermediate.
[0017] In step S2, the cobalt oxalate precursor is reduced by hydrogen to reduce the cobalt oxalate to metallic cobalt, thereby obtaining a cobalt intermediate with a stable structure.
[0018] In a preferred or optional embodiment, in step S2, the gas volume flow rate of hydrogen is 5 to 100 mL / min, and the temperature is increased after maintaining it for 20 to 40 minutes. Maintaining a certain gas flow rate can quickly remove the reduction product.
[0019] In a preferred or optional embodiment, in step S2, the temperature of the tube furnace is raised to 100-550° C. at a heating rate of 1-10° C. / min, and the holding time is 1-5 hours. At high temperatures, hydrogen has high reducing properties, and the temperature and holding time are limited to ensure that the cobalt oxalate precursor is completely reduced to a cobalt intermediate.
[0020] In a preferred or optional embodiment, the concentration of the nickel salt solution is 10-30 mM, and the solute in the nickel salt solution is selected from any one or more combinations of nickel sulfate, nickel nitrate, and nickel chloride.
[0021] In a preferred or optional embodiment, in step S3, the reaction temperature of the epitaxial growth is 20 to 60° C., and the reaction time is 20 to 80 hours.
[0022] Step S3 epitaxially grows cobalt-nickel nanostructures on the surface of the cobalt intermediate of cobalt by means of corrosion, reduction, ion exchange, etc. The metal activity of metal cobalt is strong, so nickel ions can etch metal cobalt to produce cobalt ions, and cobalt-nickel hydroxide is epitaxially grown on the surface of the cobalt substrate in the presence of dissolved oxygen, thereby forming a stable nickel-cobalt skin-core structure. The type, concentration, reaction time, and reaction temperature of the nickel salt are important parameters for forming a nickel-cobalt skin-core structure catalyst. Within the above-mentioned limited range, a nickel-cobalt skin-core structure catalyst rich in catalytic active sites and high catalytic activity can be obtained.
[0023] The third aspect of the present invention provides the use of the above nickel-cobalt skin-core structure catalyst for electrocatalytic oxidation of furan compounds.
[0024] In a preferred or optional embodiment, a nickel-cobalt skin-core structure catalyst is used as a working electrode, the catalytic electrolyte is potassium hydroxide and / or sodium hydroxide solution, and the catalytic substrate is a furan compound, including 2,5-furan dimethanol, 5-hydroxymethylfurfural, 2,5-diformylfuran, 5-hydroxymethyl-2-furancarboxylic acid, 5-formyl-2-furancarboxylic acid, furfural, furfuryl alcohol, etc.
[0025] In summary, compared with the prior art, the present invention has the following beneficial effects:
[0026] The metal cobalt substrate of the nickel-cobalt skin-core structure catalyst of the present invention has high conductivity, the surface micro-nano cobalt component makes the electrochemical starting potential of the catalyst lower, the introduction of the nickel component makes the catalyst have a high current density, the construction of the cobalt-nickel micro-nano structure greatly enhances the reaction activity of the catalyst, and the prepared catalyst has excellent industrial application prospects;
[0027] The preparation method of the nickel-cobalt skin-core structure catalyst of the present invention is simple to operate and highly repeatable, and a high-activity catalyst can be obtained without using precious metals; the micro-nano structure catalyst obtained by in-situ epitaxial growth has both good structural stability and a larger specific surface area, thereby exposing more active sites and improving the activity of the catalyst;
[0028] The nickel-cobalt skin-core structure catalyst of the present invention has a stable structure, multiple catalytic active sites, and high catalytic activity. It has high catalytic activity for furan compounds, can meet the current density required for industrial production, and can prepare high-purity FDCA. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of the cobalt oxalate precursor in Example 1 of the present invention.
[0030] Figure 2 This is a scanning electron microscope image of the nickel-cobalt skin-core structure catalyst in Example 1 of the present invention.
[0031] Figure 3 The transmission electron microscope image and high-angle annular dark field image of the nickel-cobalt skin-core structure catalyst in Example 1 of the present invention are shown.
[0032] Figure 4 Element distribution diagram of the nickel-cobalt skin-core structure catalyst in Example 1 of the present invention.
[0033] Figure 5 This is the linear sweep voltammogram of the nickel-cobalt skin-core structure catalyst in Example 9 of the present invention in an electrolyte.
[0034] Figure 6 This is a graph showing the results of electrocatalytic oxidation of HMF to produce FDCA using the nickel-cobalt skin-core structure catalyst in Example 9 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0038] The specific embodiment of the present invention provides a nickel-cobalt skin-core structure catalyst, which is prepared by the following method:
[0039] S1. Immersing a metal cobalt substrate in an oxalic acid solution, growing cobalt oxalate microwires or microrods on the surface of the metal cobalt substrate by epitaxial growth, and obtaining a cobalt oxalate precursor.
[0040] In a specific embodiment, the metal cobalt substrate is selected from any one of metal cobalt foam, cobalt sheet, cobalt foil, and cobalt mesh; the typical metal cobalt substrate is foam cobalt, and the metal cobalt substrate with a three-dimensional structure can expose more active sites, which is beneficial to enhancing the stability of the electrocatalyst.
[0041] In a specific embodiment, the solvent in the oxalic acid solution is water, and the concentration is 6-30 mM, and typical concentrations include 6 mM, 8 mM, 10 mM, 12 mM, 15 mM, 20 mM, 22 mM, 25 mM, 28 mM, 30 mM, etc. The molar ratio of the metal cobalt substrate to oxalic acid is between 1:5.5-28.
[0042] In a specific embodiment, the reaction time of the epitaxial growth in step S1 is 0.25 to 4 hours, and typical epitaxial growth times include 0.25 hours, 0.5 hours, 1 hour, 2 hours, 2.5 hours, 3 hours, 4 hours, etc. The reaction temperature of the epitaxial growth is 20 to 80° C., and typical epitaxial growth temperatures include 25° C., 35° C., 45° C., 50° C., 60° C., 80° C., etc. The epitaxial growth is carried out under mild conditions, the preparation method is simple, and it is easy to scale up for production.
[0043] S2, placing the cobalt oxalate precursor in a hydrogen atmosphere for reduction to obtain a cobalt intermediate. The specific steps are: placing the cobalt oxalate precursor in a tubular furnace, introducing hydrogen into the tubular furnace, keeping the temperature for a period of time, raising the temperature to a set temperature, then keeping the temperature, and cooling to room temperature to obtain a cobalt intermediate with a stable structure.
[0044] In a specific embodiment, the gas volume flow rate of hydrogen is 5 to 100 mL / min, and the temperature is increased after being maintained for 20 to 40 minutes.
[0045] In a specific embodiment, the tube furnace is heated to 100-550°C at a heating rate of 1-5°C / min, and the holding time is 1-5 hours. At high temperatures, hydrogen has high reducing properties, and the temperature and holding time are limited to ensure that the cobalt oxalate precursor is completely reduced to a cobalt intermediate.
[0046] S3. Immerse the cobalt intermediate in a nickel salt solution, and epitaxially grow cobalt nickel hydroxide on the surface of the cobalt microwires or microrods to obtain a nickel-cobalt skin-core structure catalyst.
[0047] In a specific embodiment, the solution of the nickel salt solution is water, and the solute is selected from any one or more combinations of nickel sulfate, nickel nitrate, and nickel chloride, preferably nickel nitrate.
[0048] In a specific embodiment, the concentration of the nickel salt solution is 10-30 mM, and typical concentrations include 10 M, 12 M, 15 M, 20 M, 22 M, 25 M, 30 M, etc.
[0049] In a specific embodiment, the reaction temperature of the epitaxial growth in step S3 is 20-60°C, and typical reaction temperatures include 20°C, 22°C, 25°C, 28°C, 30°C, 45°C, 58°C, etc. The reaction time of the epitaxial growth is 20-80h, and typical reaction times include 20h, 24h, 30h, 38h, 40h, 60h, 80h, etc.
[0050] The above-mentioned preparation method is simple to operate, highly repeatable, and can obtain a highly active catalyst without using precious metals; the micro-nanostructured catalyst obtained by in situ epitaxial growth has both good structural stability and a larger specific surface area, thereby exposing more active sites and improving the activity of the catalyst.
[0051] The cobalt skin-core structure catalyst prepared by the above method includes a metal cobalt substrate and a micro-nano structure grown on the metal cobalt substrate, wherein the micro-nano structure includes a core layer and a skin layer wrapping the core layer, wherein the core layer is a cobalt microwire or microrod, and the skin layer is cobalt nickel hydroxide. This micro-nano structure exposes more specific surface area and catalytic active sites than the metal cobalt substrate, cobalt microwire, and cobalt microrod, so that the catalyst has good activity; the cobalt substrate has high conductivity, the surface micro-nano cobalt component makes the electrochemical starting potential of the catalyst lower, and the introduction of the nickel component makes the catalyst have a high current density.
[0052] The specific embodiment of the present invention also provides the application of the nickel-cobalt skin-core structure catalyst, which is used for the electrocatalytic oxidation reaction of furan compounds. The specific application method is as follows: using the above electrocatalyst as a working electrode, constructing a three-electrode system in an electrolytic cell, adding an alkaline solution containing biomass as an electrolyte to the electrolytic cell, and immersing the working electrode in the electrolyte to perform the electrocatalytic oxidation reaction of biomass.
[0053] In a specific embodiment, the electrolyte is a 0.5-2M potassium hydroxide and / or sodium hydroxide solution containing biomass, and the solvent is water; the concentration of furan compounds is 1-1000mM, and typical concentrations include 10mM, 20mM, 50mM, 80mM, 100mM, 200mM, 400mM, 800mM, etc.; typical biomass includes 2,5-furan dimethanol, 5-hydroxymethylfurfural, 2,5-diformylfuran, 5-hydroxymethyl-2-furancarboxylic acid, 5-formyl-2-furancarboxylic acid, furfural, furfuryl alcohol, etc.
[0054] In a specific embodiment, the potential of the electrocatalytic oxidation is 1.35-1.8 V vs. RHE. Typical potentials include 1.35 V vs. RHE, 1.45 V vs. RHE, 1.5 V vs. RHE, 1.55 V vs. RHE, 1.6 V vs. RHE, 1.8 V vs. RHE, etc.
[0055] The above-mentioned nickel-cobalt skin-core structure catalyst has a stable structure, multiple catalytic active sites, and high catalytic activity. It has high catalytic activity for furan compounds, can meet the current density required for industrial production, and can prepare high-purity FDCA. It has high economic value and good industrial application prospects.
[0056] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0057] Example 1
[0058] (1) Take 0.5×3cm 2 Cobalt foams of different sizes were ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min each, and dried for later use.
[0059] (2) The cleaned cobalt foam was immersed in 50 ml of 22 mM oxalic acid solution and allowed to stand for reaction at 50 °C for 2 h. After the reaction was completed, it was taken out, cleaned with deionized water, and dried in an oven at 80 °C for 2 h to obtain a cobalt oxalate precursor. The microscopic morphology of the cobalt oxalate precursor is shown in FIG. Figure 1 shown.
[0060] (3) The cobalt oxalate precursor is placed in a tubular furnace with a hydrogen atmosphere at a flow rate of 5 ml / min, maintained for 30 min, heated to 500° C. at a heating rate of 5° C. / min, maintained for 2 h, and then cooled to room temperature to obtain a cobalt intermediate.
[0061] (4) The cobalt intermediate was immersed in a 10 mM nickel nitrate solution, allowed to stand, and reacted at a constant temperature of 25°C for 38 hours. After the reaction was completed, it was taken out, cleaned with deionized water, and placed in an oven at 80°C for 2 hours to obtain a nickel-cobalt skin-core structure catalyst. The scanning electron microscope image of the nickel-cobalt skin-core structure catalyst is shown in FIG. Figure 2 The transmission electron microscopy image of the nickel-cobalt skin-core structure catalyst is shown in Figure 3 As shown in a, the high-angle annular dark field image of the nickel-cobalt skin-core structure catalyst is shown in Figure 3 b shows the element distribution diagram of the nickel-cobalt skin-core structure catalyst. Figure 4 shown.
[0062] Example 2
[0063] (1) Take 0.5×3cm 2 Cobalt foams of different sizes were ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min each, and dried for later use.
[0064] (2) The cleaned cobalt foam was immersed in 50 ml of 8 mM oxalic acid solution and allowed to stand for constant temperature reaction at 80° C. for 2 h. After the reaction was completed, the foam was taken out, cleaned with deionized water, and dried in an oven at 80° C. for 2 h to obtain a cobalt oxalate precursor.
[0065] (3) The cobalt oxalate precursor is placed in a tubular furnace with a hydrogen atmosphere at a flow rate of 5 ml / min, maintained for 30 min, heated to 500° C. at a heating rate of 5° C. / min, maintained for 2 h, and then cooled to room temperature to obtain a cobalt intermediate.
[0066] (4) The cobalt intermediate was immersed in a 20 mM nickel nitrate solution, allowed to stand, and reacted at a constant temperature of 25° C. for 38 hours. After the reaction was completed, it was taken out, cleaned with deionized water, and placed in an oven at 80° C. for 2 hours to obtain a nickel-cobalt skin-core structure catalyst.
[0067] Example 3
[0068] (1) Take 0.5×3cm 2Cobalt foams of different sizes were ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min each, and dried for later use.
[0069] (2) The cleaned cobalt foam was immersed in 50 ml of 22 mM oxalic acid solution and allowed to stand for constant temperature reaction at 80° C. for 2 h. After the reaction was completed, the foam was taken out, cleaned with deionized water, and dried in an oven at 80° C. for 2 h to obtain a cobalt oxalate precursor.
[0070] (3) The cobalt oxalate precursor is placed in a tubular furnace with a hydrogen atmosphere at a flow rate of 5 ml / min, maintained for 30 min, heated to 500° C. at a heating rate of 5° C. / min, maintained for 2 h, and then cooled to room temperature to obtain a cobalt intermediate.
[0071] (4) The cobalt intermediate was immersed in a 30 mM nickel nitrate solution, allowed to stand, and reacted at a constant temperature of 25° C. for 38 hours. After the reaction was completed, it was taken out, cleaned with deionized water, and placed in an oven at 80° C. for 2 hours to obtain a nickel-cobalt skin-core structure catalyst.
[0072] Example 4
[0073] (1) Take 0.5×3cm 2 Cobalt sheets of different sizes were ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min each, and dried for later use.
[0074] (2) The cleaned cobalt sheet was immersed in 50 ml of 22 mM oxalic acid solution and allowed to stand for reaction at 80° C. for 2 h. After the reaction was completed, the sheet was taken out, cleaned with deionized water, and dried in an oven at 80° C. for 2 h to obtain a cobalt oxalate precursor.
[0075] (3) The cobalt oxalate precursor is placed in a tubular furnace with a hydrogen atmosphere at a flow rate of 5 ml / min, maintained for 30 min, heated to 500° C. at a heating rate of 5° C. / min, maintained for 2 h, and then cooled to room temperature to obtain a cobalt intermediate.
[0076] (4) The cobalt intermediate was immersed in a 30 mM nickel nitrate solution, allowed to stand, and reacted at a constant temperature of 25° C. for 38 hours. After the reaction was completed, it was taken out, cleaned with deionized water, and placed in an oven at 80° C. for 2 hours to obtain a nickel-cobalt skin-core structure catalyst.
[0077] Example 5
[0078] (1) Take 0.5×3cm 2 Cobalt foils of different sizes were ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min each, and dried for later use.
[0079] (2) The cleaned cobalt foil was immersed in 50 ml of 8 mM oxalic acid solution and allowed to stand for reaction at 20° C. for 2 h. After the reaction was completed, the foil was taken out, cleaned with deionized water, and dried in an oven at 80° C. for 2 h to obtain a cobalt oxalate precursor.
[0080] (3) The cobalt oxalate precursor is placed in a tubular furnace with a hydrogen atmosphere at a flow rate of 5 ml / min, maintained for 30 min, heated to 200° C. at a heating rate of 5° C. / min, maintained for 2 h, and then cooled to room temperature to obtain a cobalt intermediate.
[0081] (4) The cobalt intermediate was immersed in a 10 mM nickel sulfate solution, allowed to stand, and reacted at a constant temperature of 25° C. for 38 hours. After the reaction was completed, it was taken out, cleaned with deionized water, and placed in an oven at 80° C. for 2 hours to obtain a nickel-cobalt skin-core structure catalyst.
[0082] Example 6
[0083] (1) Take 0.5×3cm 2 Cobalt foams of different sizes were ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min each, and dried for later use.
[0084] (2) The cleaned cobalt foam was immersed in 50 ml of 8 mM oxalic acid solution and allowed to stand for constant temperature reaction at 35° C. for 2 h. After the reaction was completed, the foam was taken out, cleaned with deionized water, and dried in an oven at 80° C. for 2 h to obtain a cobalt oxalate precursor.
[0085] (3) The cobalt oxalate precursor is placed in a tubular furnace with a hydrogen atmosphere at a flow rate of 5 ml / min, maintained for 30 min, heated to 300 °C at a heating rate of 5 °C / min, and kept for 2 h, then cooled to room temperature to obtain a cobalt intermediate.
[0086] (4) The cobalt intermediate was immersed in a 10 mM nickel sulfate solution, allowed to stand, and reacted at a constant temperature of 25° C. for 24 hours. After the reaction was completed, it was taken out, cleaned with deionized water, and placed in an oven at 80° C. for 2 hours to obtain a nickel-cobalt skin-core structure catalyst.
[0087] Example 7
[0088] (1) Take 0.5×3cm 2 Cobalt sheets of different sizes were ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min each, and dried for later use.
[0089] (2) The cleaned cobalt foil was immersed in 50 ml of 16 mM oxalic acid solution and allowed to stand for reaction at 20° C. for 2 h. After the reaction was completed, the foil was taken out, cleaned with deionized water, and dried in an oven at 80° C. for 2 h to obtain a cobalt oxalate precursor.
[0090] (3) The cobalt oxalate precursor is placed in a tubular furnace with a hydrogen atmosphere at a flow rate of 5 ml / min, maintained for 40 min, heated to 300° C. at a heating rate of 5° C. / min, maintained for 2 h, and then cooled to room temperature to obtain a cobalt intermediate.
[0091] (4) The cobalt intermediate was immersed in a 10 mM nickel chloride solution, allowed to stand, and reacted at a constant temperature of 25° C. for 20 hours. After the reaction was completed, it was taken out, cleaned with deionized water, and placed in an oven at 80° C. for 2 hours to obtain a nickel-cobalt skin-core structure catalyst.
[0092] Example 8
[0093] (1) Take 0.5×3cm 2 Cobalt foils of different sizes were ultrasonically cleaned with deionized water and anhydrous ethanol for 10 min each, and dried for later use.
[0094] (2) The cleaned cobalt foil was immersed in 50 ml of 8 mM oxalic acid solution and allowed to stand for constant temperature reaction at 80° C. for 2 h. After the reaction was completed, the foil was taken out, cleaned with deionized water, and dried in an oven at 80° C. for 2 h to obtain a cobalt oxalate precursor.
[0095] (3) The cobalt oxalate precursor is placed in a tubular furnace with a hydrogen atmosphere at a flow rate of 5 ml / min, maintained for 40 min, heated to 200° C. at a heating rate of 5° C. / min, maintained for 2 h, and then cooled to room temperature to obtain a cobalt intermediate.
[0096] (4) The cobalt intermediate was immersed in a 20 mM nickel nitrate solution, allowed to stand, and reacted at a constant temperature of 25° C. for 24 hours. After the reaction was completed, it was taken out, cleaned with deionized water, and placed in an oven at 80° C. for 2 hours to obtain a nickel-cobalt skin-core structure catalyst.
[0097] Example 9
[0098] (1) The nickel-cobalt skin-core structure catalyst prepared in Example 1 was installed on an electrochemical workstation as an anode.
[0099] (2) The electrolyte was 20 ml of 1 M KOH solution, the counter electrode was a platinum sheet, the reference electrode was a mercury oxide electrode, and the area of the catalyst immersed in the electrolyte was 1 × 0.5 cm 2 The mixture was stirred with a magnetic stirrer at a speed of 600 rpm.
[0100] (3) The LSV curve was obtained using the linear scanning method of the electrochemical workstation with a scanning rate of 5 mV / s.
[0101] (4) HMF was added to the electrolyte to a concentration of 10 mM, and the LSV curve was obtained at a scan rate of 5 mV / s.
[0102] (5) HMF was added to the electrolyte to a concentration of 100 mM, and the LSV curve was obtained at a scan rate of 5 mV / s. The LSV curves in the above steps 3), 4), and 5) are as follows: Figure 5 As shown, the results show that the catalyst of Example 1 has a very high current density, and its performance far exceeds the industrial current density standard.
[0103] (6) Electrolysis was performed in 5 mL of an electrolyte solution containing 1 M KOH and 10 mM HMF using a constant potential mode at an electrolysis potential of 1.35 V vs. RHE. The electrolysis results are shown in Figure 6 As shown, the catalyst of Example 1 has very high HMF conversion rate and FDCA yield at low potential, with the HMF conversion rate reaching 95.8% and the FDCA yield reaching 91.3%.
[0104] Example 10
[0105] (1) The nickel-cobalt skin-core structure catalyst prepared in Example 1 was installed on an electrochemical workstation as an anode.
[0106] (2) The electrolyte was 20 ml of 1 M KOH solution, the counter electrode was a platinum sheet, the reference electrode was a mercury oxide electrode, and the area of the catalyst immersed in the electrolyte was 1 × 0.5 cm 2 The mixture was stirred with a magnetic stirrer at a speed of 600 rpm.
[0107] (3) The LSV curve was obtained using the linear scanning method of the electrochemical workstation with a scanning rate of 5 mV / s.
[0108] (4) BHMF was added to the electrolyte to a concentration of 10 mM, and the LSV curve was obtained at a scan rate of 5 mV / s.
[0109] (5) BHMF was added to the electrolyte to a concentration of 100 mM, and the LSV curve was obtained at a scan rate of 5 mV / s.
[0110] (6) Electrolysis was performed in a 5 mL electrolyte solution containing 1 M KOH and 10 mM BHMF using a constant potential mode at an electrolysis potential of 1.35 V vs. RHE. The electrolysis results showed that the catalyst of Example 1 had an HMF conversion rate of 93.6% and an FDCA yield of 90.2% at a low potential.
[0111] Embodiment 11
[0112] The difference between this example and Example 9 is that the nickel-cobalt skin-core structure catalyst prepared in Example 2 is used as the anode of the electrochemical workstation, and electrolysis is performed in a constant potential mode in 5 mL of an electrolyte containing 1 M KOH and 20 mM 2,5-diformylfuran, and the electrolysis potential is 1.45 V vs. RHE. The electrolysis results show that the conversion rate of 2,5-diformylfuran is 94.8%, and the FDCA yield is 89.9%.
[0113] Example 12
[0114] The difference between this example and Example 9 is that the nickel-cobalt skin-core structure catalyst prepared in Example 3 is used as the anode of the electrochemical workstation, and electrolysis is performed in a constant potential mode in 5 mL of an electrolyte containing 1 M KOH and 50 mM 5-hydroxymethyl-2-furancarboxylic acid, and the electrolysis potential is 1.55 V vs. RHE. The electrolysis results show that the conversion rate of 5-hydroxymethyl-2-furancarboxylic acid is 90.4%, and the FDCA yield is 86.8%.
[0115] Example 13
[0116] The difference between this example and Example 9 is that the nickel-cobalt skin-core structure catalyst prepared in Example 4 is used as the anode of the electrochemical workstation, and electrolysis is performed in a constant potential mode in 5 mL of an electrolyte containing 1 M KOH and 80 mM 5-formyl-2-furancarboxylic acid, and the electrolysis potential is 1.6 V vs. RHE. The electrolysis results show that the conversion rate of 5-formyl-2-furancarboxylic acid is 94.7%, and the FDCA yield is 91.0%.
[0117] Embodiment 14
[0118] The difference between this example and Example 9 is that the nickel-cobalt skin-core structure catalyst prepared in Example 5 is used as the anode of the electrochemical workstation, and electrolysis is performed in a constant potential mode in 5 mL of an electrolyte containing 1 M KOH and 100 mM furfural, and the electrolysis potential is 1.8 V vs. RHE. The electrolysis results show that the furfural conversion rate is 88.6% and the FDCA yield is 84.3%.
[0119] Embodiment 15
[0120] The difference between this example and Example 9 is that the nickel-cobalt skin-core structure catalyst prepared in Example 6 is used as the anode of the electrochemical workstation, and electrolysis is performed in a constant potential mode in 5 mL of an electrolyte containing 1 M KOH and 20 mM furfuryl alcohol, and the electrolysis potential is 1.35 V vs. RHE. The electrolysis results show that the furfural conversion rate is 89.2% and the FDCA yield is 86.1%.
[0121] Example 16
[0122] The difference between this example and Example 9 is that the nickel-cobalt skin-core structure catalyst prepared in Example 7 is used as the anode of the electrochemical workstation, and electrolysis is performed in a constant potential mode in 5 mL of an electrolyte containing 1 M KOH and 20 mM HMF, and the electrolysis potential is 1.35 V vs. RHE. The electrolysis results show that the HMF conversion rate is 93.9% and the FDCA yield is 90.2%.
[0123] Embodiment 17
[0124] The difference between this example and Example 9 is that the nickel-cobalt skin-core structure catalyst prepared in Example 8 is used as the anode of the electrochemical workstation, and electrolysis is performed in a constant potential mode in 5 mL of an electrolyte containing 1 M KOH and 20 mM BHMF, and the electrolysis potential is 1.35 V vs. RHE. The electrolysis results show that the BHMF conversion rate is 95.9% and the FDCA yield is 92.3%.
[0125] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A nickel-cobalt skin-core structure catalyst, characterized in that: The invention comprises a metal cobalt substrate and a micro-nano structure grown on the metal cobalt substrate, wherein the micro-nano structure comprises a core layer and a skin layer wrapping the core layer, wherein the core layer is a cobalt micron wire or micron rod, and the skin layer is cobalt nickel hydroxide. The preparation method of the nickel-cobalt skin-core structure catalyst comprises the following steps: S1, immersing a metal cobalt substrate in an oxalic acid solution, and growing cobalt oxalate microwires or microrods on the surface of the metal cobalt substrate by epitaxial growth to obtain a cobalt oxalate precursor; S2, placing the cobalt oxalate precursor in a hydrogen atmosphere for reduction to obtain a cobalt intermediate; S3. Immerse the cobalt intermediate in a nickel salt solution, and epitaxially grow cobalt nickel hydroxide on the surface of the cobalt microwires or microrods to obtain a nickel-cobalt skin-core structure catalyst.
2. A method for preparing a nickel-cobalt skin-core structure catalyst as claimed in claim 1, characterized in that: The following steps are involved: S1, immersing a metal cobalt substrate in an oxalic acid solution, and growing cobalt oxalate microwires or microrods on the surface of the metal cobalt substrate by epitaxial growth to obtain a cobalt oxalate precursor; S2, placing the cobalt oxalate precursor in a hydrogen atmosphere for reduction to obtain a cobalt intermediate; S3. Immerse the cobalt intermediate in a nickel salt solution, and epitaxially grow cobalt nickel hydroxide on the surface of the cobalt microwires or microrods to obtain a nickel-cobalt skin-core structure catalyst.
3. The method for preparing the nickel-cobalt skin-core structure catalyst according to claim 2, characterized in that: In the step S1, the molar ratio of the metal cobalt substrate to the oxalic acid is 1:5.5-28.
4. The method for preparing the nickel-cobalt skin-core structure catalyst according to claim 3, characterized in that: In the step S1, the reaction time of the epitaxial growth is 0.25-4 h, and the reaction temperature is 20-80° C.
5. The method for preparing the nickel-cobalt skin-core structure catalyst according to claim 2, characterized in that: The step S2 specifically includes: placing the cobalt oxalate precursor into a tubular furnace, introducing hydrogen into the tubular furnace, heating the furnace to a set temperature after a period of time, then maintaining the temperature, and cooling the temperature to room temperature, thereby obtaining a cobalt intermediate.
6. The method for preparing the nickel-cobalt skin-core structure catalyst according to claim 5, characterized in that: In step S2, the gas volume flow rate of hydrogen is 5-100 mL / min, and the temperature is increased after maintaining it for 20-40 minutes.
7. The method for preparing the nickel-cobalt skin-core structure catalyst according to claim 5, characterized in that: In the step S2, the temperature of the tube furnace is raised to 100-550° C. at a heating rate of 1-10° C. / min, and the holding time is 1-5 hours.
8. The method for preparing the nickel-cobalt skin-core structure catalyst according to claim 2, characterized in that: In step S3, the concentration of the nickel salt solution is 10-30 mM, and the solute in the nickel salt solution is selected from any one or more combinations of nickel sulfate, nickel nitrate, and nickel chloride.
9. The method for preparing the nickel-cobalt skin-core structure catalyst according to claim 8, characterized in that: In the step S3, the reaction temperature of the epitaxial growth is 20-60° C., and the reaction time is 20-80 hours.
10. An application of a nickel-cobalt skin-core structure catalyst, characterized in that: The nickel-cobalt skin-core structure catalyst as claimed in claim 1 is used for electrocatalytic oxidation of furan compounds.
